'Flip-flap' hernia sac sandwich mesh hernioplasty for giant incisional hernia. (April 2023) - Kothari, Maulik; Somashekhar, Uday; Kothari, Reena; Thakur, Dileep Singh; Agarwal, Pawan; Sharma, Dhananjaya
Purpose: The treatment of giant ventral hernia (GVH) with domain loss is a challenge for surgeons. This modified and simplified form of sandwich technique in a form of flip-flap repair was done to assess the outcomes of GVH repair by using the hernia sac taking into account the late complications in terms of recurrence, mesh explantation and early: SSO (surgical site occurrence).Material and method: A total of 21 patients of GVH were treated with flip-flap repair technique in the department of surgery in a teaching hospital in the central India between December 16 to June 21. In flip-flap technique the hernia sac is tailored in the best possible way, by making multiple layered flaps encasing the Polypropylene mesh in between, separating it from intraperitoneal contents and subcutaneous tissue.Results: In this prospective and interventional study, the collected data revealed the mean follow up period of 22.3 months (7months to 48months). Mean age was 44.2years (27-65 years). SSO was seen in 38% of cases mainly in the form of SSI. No explantation of mesh and recurrence was seen in any patient.Conclusion: The flip-flap repair technique is safe and effective surgical technique that can be used for the treatment of GVH regardless of the size, BMI or position of hernia.